Implementasi Keselamatan Kerja di Pertambangan melalui Penerapan Sistem Manajemen K3 Berbasis ISO 45001 - Aura Fariza Yulianti Saputri; Zahwa Rahmanda Aulya; Angel Caroline; Laura Aulia Rosaline (Journal of Educational Innovation and Public Health, 2024)
In the mining world, the implementation of an Occupational Health and Safety System (K3) based on ISO 45001 has become the main focus for improving workplace safety. This research will discuss how the implementation of ISO 45001 can support the development of a work environment that is responsive, adaptable and pays attention to employee welfare amidst the complex challenges faced by the mining industry. This research will also produce the benefits and process of implementing ISO 45001 in the mining industry.